Analisis Strategi Pemasaran Digital Terhadap Loyalitas Konsumen - Siti Syakira Hasna Kamila; Halimah Zahrah; Rina Pitria; Rasyad Khairan (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
Digital marketing strategies have become essential in shaping consumer loyalty in the era of social media. This study aims to analyze the impact of PT Kanzler’s digital strategy on TikTok on consumer loyalty, focusing on content marketing, influencer marketing, and electronic word of mouth (e-WOM). Using a qualitative descriptive method through literature review, the research explores how these digital strategies foster emotional engagement and consumer trust, as well as how the principles of marketing ethics, namely transparency, honesty, and social responsibility, can play a role in building authentic loyalty. The findings indicate that content marketing and influencer marketing significantly affect consumer loyalty, while e-WOM appears to have a weaker impact. Ethically implemented digital strategies help prevent superficial loyalty driven by viral content. Thus, digital marketing requires not only creativity but also integrity to establish long-term, mutually beneficial relationships between brands and consumers.